(untitled) (Ames, Iowa, 2006)
The book comprehensively covers the most important aspects of milk production including: trends and methods of raw milk production in different regions; compositional, nutritional, therapeutic, physico-chemical, and microbiological characteristics of the milks; processing technology; and types, distribution and consumption of the manufactured products from minor species milks. Of special note is coverage comparing specific human health attributes of milk from the various species, including nutritional, allergenic, immunological, and cultural factors. Because secondary dairy species have such a significant impact on human well-being and survival in many parts of the world, the Handbook of Milk of Non-Bovine Mammals is an essential reference book of leading-edge information for dairy scientists, nutritionists, food chemists, allergy specialists, health professionals, and allied professionals
Keywords: Milk.,Livestock,Dairying,Gia súc,Sữa,Bơ sữa